THE STUDY OF SPIRITUAL EDUCATION IN SEYYED HOSEIN NASRS' WORKS AND COMPARING IT WITH SOME CURRENT DEFINITIONS - Shamshiri, Babak; Rahimian, Saeed; Tajali Ardekani, Hosein Ali (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
The aim of this article is to probe the concept of spiritual education in Seyyed Hosein Nasr`s thoughts and to compare it with the current definitions of the concept. This study has been done through the qualitative method called transcendental analysis. Therefore, that concept was conceptualized through investigating and eliciting the requisite assumptions from Nasr`s philosophical approach. Findings showed that in Nasr`s thoughts, spiritual education is the process of actualizing all the innate potentialities of human as a whole towards his or her monotheistic nature through developing knowledge, love, righteous actions and acquiring virtues to transcend his or her existential layers to train his or her spirit, to know the Ultimate Reality and to return to his or her prototype in God. It is acquirable by taking action based on a heavenly religion. The aim of spiritual education is to know the Ultimate Reality intuitively. Compared to the current definitions, the concluded concept is more similar to that of Carr’s and Tabatabaie’s ideas while it is different from Miller, Duff and Bigger’s perspectives.